Tratamiento contable de la cuenta propiedad planta y equipo de la empresa ALTEC S.A de la ciudad de Babahoyo - Casanova Rivas, Adriana Lisseth (2020)
The present case study entitled accounting treatment of property, plant and equipment of the company ALTEC SA, is intended to determine the accounting reality of the fixed assets of the organization, especially in relation to the depreciation process, where life should be considered useful, the depreciation percentages and the residual or salvage value, as it is also called. It has been determined that this company ALTEC S.A. It should not apply the full Rules, but for SMEs, because they can be efficiently carried out in the registry, because they only have 300 items of disclosures and that the basic financial statements do not have greater differentiation with the traditional ones. The document also indicates that the initial measurement is carried out at fair value plus transaction costs and the subsequent measurement is according to the amortized cost.